EFIKASI DIRI DAN SELF DIRECTED LEARNING READINESS PADA MAHASISWA KEDOKTERAN - Supriyati Supriyati; Sri Maria Puji Lestari; Eneng Wulandari (JURNAL PSIKOLOGI MALAHAYATI, 2019)
SELF EFFICACY AND SELF DIRECTED LEARNING READINESS AMONG MEDICAL STUDENTSNowadays, Medical Faculty uses Problem Based Learning (PBL) method in learning. PBL uses problem or case examples as a triggers to discuss medical learning material. The application of PBL can produce self directed learning readiness (SDLR) in the learning process. SDLR was measured on the basis of an indicator to the extent that a person knows his or her attitudes, skills and personal characteristics to undergo independent learning The application of the SDLR is influenced by two factors, external and internal. One of the internal factors affecting SDLR is Self-efficacy. The purpose of this study was to find relationship between self efficacy and self directed learning readiness among medical students. This study was a quantitative study with analytic design and cross sectional approach. The subject of this study was 185 medical students of Malahayati University grade 2016. The instruments used in this study was general self efficacy scale and self directed learning readiness scale. Based on the data analysis it was found that there is a significant relationship between self efficacy and SDLR among medical student of Malahayati University grade 2016 (r = .664, p < .005). The result of this study has implication on high education institusion especially medical faculty to build high students’ self efficacy and for further research need ti study other factors that relates with SDLR.Saat ini Fakultas Kedokteran menggunakan metode belajar Problem Based Learning (PBL). PBL menggunakan masalah atau contoh kasus sebagai pemicu untuk membahas materi pembelajaran kedokteran. Pengaplikasian PBL dapat menghasilkan self directed learning readiness (SDLR) dalam proses belajar. SDLR diukur berdasarkan indikator sejauh mana seseorang mengetahui tetang sikap, keterampilan dan karakteristik pribadinya untuk melaksanakan pembelajaran mandiri. Pengaplikasian SDLR dipengaruhi oleh dua faktor, eksternal dan internal. Salah satu faktor internal yang mempengaruhi SDLR adalah Efikasi diri. Penelitian ini bertujuan untuk meneliti hubungan antara efikasi diri dengan self directed learning readiness pada mahasiswa kedokteran. Jenis penelitian ini adalah kuantitatif dengan desain analitik dan pendekatan cross sectional. Subjek penelitian adalah 186 mahasiswa Fakultas Kedokteran Universitas Malahayati Bandar Lampung angkatan 2016. Alat untuk mengukur efikasi diri yang digunakan adalah General Self Eficacy dan Self Directed Learning Readiness (SDLR). Berdasarkan analisis data ditemukan bahwa terdapat hubungan yang signifikan antara efikasi diri dengan SDLR pada Mahasiswa Fakultas Kedokteran Umum angkatan 2016 (r = .664, p < .005).  Hasil penelitian ini memiliki implikasi pada institusi pendidikan tinggi khususnya fakultas kedokteran untuk membina mahasiswanya memiliki efikasi diri yang tinggi serta untuk penelitian selanjutnya agar meneliti faktor lain yang berhubungan dengan SDLR.